Dinamika Ijtihad dalam Lembaga Fatwa Kontemporer: Perspektif Ushul Fikih dan Kontekstualisasi Ijtihad - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study examines the role of mujtahids within the Hanafi and Hanbali schools through a comparative ushul al-fiqh perspective, emphasizing their relevance for the contextualization of ijtihad. It argues that the Hanafi model prioritizes rationality and adaptability through ra’y, qiyas, and istihsan, enabling flexible responses to social realities. In contrast, the Hanbali approach emphasizes textual fidelity and methodological caution, ensuring normative consistency. However, later developments in Hanbali thought incorporate maqāṣid-oriented reasoning. The study concludes that integrating both rational and textual approaches allows Islamic law to remain adaptive, credible, and responsive to contemporary legal challenges. Keywords: Mujtahid, Ijtihad, Ushul al-Fiqh